Multilateral collaboration between technical communicators and translators: a case study of new technologies and processes - Sonia Vandepitte; Bruce Maylath; Birthe Mousten; Patricia Minacori; Suvi Isohella (JoSTrans: The Journal of Specialised Translation)
This article describes a multilateral international project (Thompson and Carter 1973, Moreno-Lopez 2004) in technical communication and translator training programmes and discusses its use of technologies in what is seen as the largest and most complex international learning-by-doing collaboration to date. The project is a student collaboration involving two sets of cross-cultural virtual teams who either translate from Danish and Dutch into English and review (or edit) into American English or who are involved in international collaborative writing by Spaniards and Americans, usability testing by Finnish students, and translation from English into Dutch, French and Italian (Humbley et al. 2005; Maylath et al. 2008; Mousten et al. 2008; Mousten; Vandepitte et al. 2010; Mousten et al. 2010, Mousten et al. 2012, Maylath et al. 2013, Maylath et al. 2013b). While students use email, iChat and Skype to communicate with each other and carry out their assignments, they also explore revision and translation reviewing activities on Google Drive. Their comments and negotiations made explicit in Google Drive documents can then be assessed by teachers, who also employ other Google Drive documents to update both the scripts for the two translation directions and the student-topic database. The project culminates in multilateral videoconferences that summarise the main aspects of learning by students. As the collaboration closely resembles the complexity of the international documentation workplaces of language service providers, the use of the various technologies proves to be a central element both in the students' activities and in the teachers' guidance.